The Role Of The Polri Criminal Reserve Unit In Revealing Cases Of Motorcycle Theft (Case Study Of Polres Semarang) - Berry Ballen Saputra; Azis Budianto; Riswadi Riswadi (Publikasi Indonesia, 2023)
The increase in vehicle theft cannot be stopped due to the increasing growth rate of vehicles which is quite lofty in urban and rural areas. The growth rate of motorized vehicles is not proportional to the growth of roads or the length of roads available. Such conditions will indirectly affect the development of urban planning. The evidenced by the limited land or sufficient motorized vehicle parking pockets that people are no longer aware of safety factors in parking their vehicles and their concern for other road users. Negligence in paying attention to safety factors in parking a vehicle will facilitate the crime of motor vehicle theft. Roadside parking lots and shopping centers are places that are most vulnerable or often targeted by motor vehicle theft perpetrators. For it, the community must take preventive efforts, not just rely on security forces to overcome, or minimize opportunities for motor vehicle theft. Involving the community carries out security such as night patrols or night watch because at night it is considered very vulnerable compared to other moments of vehicle theft that happen in society when bearing the eradication of crime, the police sometimes encounter various obstacles. The role and responsibility of the Police Investigator are expected by the public to uncover cases of vehicle theft that are considered not optimal by the community because all the people who report to the authorities, here are the police, and only a small part is followed up. The type of research is normative research.